Effect of Arm Movement and Task Difficulty on Balance Performance in Children, Adolescents, and Young Adults - Muehlbauer, Thomas; Hill, Mathew W.; Heise, Joana; Abel, Leander; Schumann, Ina; Brueckner, Dennis; Schedler, Simon (Frontiers in Human Neuroscience, 2022)
Background Studies have shown that restricted compared to free arm movement negatively affects balance performance during balance assessment and this is reinforced when the level of task difficulty (e.g., varying stance/walk conditions, sensory manipulations) is increased. However, it remains unclear whether these findings apply to individuals with differences in the development of the postural control system. Thus, we examined the influence of arm movement and task difficulty on balance performance in children, adolescents, and young adults. Methods Static, dynamic, and proactive balance performance were assessed in 40 children (11.5 ± 0.6 years), 30 adolescents (14.0 ± 1.1 years), and 41 young adults (24.7 ± 3.0 years) using the same standardized balance tests [i.e., one-legged stance (OLS) time with eyes opened/closed and/or on firm/foam ground, 3-m beam (width: 6, 4.5, or 3 cm) walking backward step number, Lower Quarter Y-Balance test (YBT-LQ) reach distance] with various difficulty levels under free vs. restricted arm movement conditions. Results In all but one test, balance performance was significantly better during free compared to restricted arm movement. Arm by age interactions were only observed for the YBT-LQ and post hoc analyses revealed significantly greater performance differences between free and restricted arm movement, especially, in young adults. Arm by age by task difficulty interactions were found for the OLS and the 3-m beam walking backward test. Post hoc analyses showed significantly greater performance differences between free and restricted arm movement during high vs. low levels of task difficulty and this was more pronounced in children and adolescents. Conclusions Regardless of age, static, dynamic, and proactive balance performance benefited from arm movements and this was especially noted for youth performing difficult balance tasks.